Pelatihan Perintisan Jemaat Melalui Penginjilan Kontekstual Budaya Mayoritas di Gereja Kristen Nazarene Siloam Weleri - Wahyudi Wijayanto; Rudyanto Chandra Saputra; Rini Adiyati; Sunarti (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
This Community Service Program (PkM) was implemented to address the needs of the Church of the Nazarene Siloam Weleri in strengthening the congregation’s capacity for contextual evangelism within a majority-religion cultural environment. The training was designed to equip church members with theological foundations, evangelistic strategies, and practical skills through four main topics: soul outreach through the gifts of the Holy Spirit, proclamation of the Good News, Christian maturity in holistic outreach, and a contextual pastoral counseling approach. A qualitative field method was employed through needs-assessment interviews, structured seminars, mentoring sessions, and final evaluation. The results indicate a significant increase in the congregation’s understanding and practice of contextual evangelism. This is reflected in personal testimonies, the establishment of new fellowship groups, and initial discipleship initiatives. Although challenges remain—particularly related to time management and direct evangelism skills—the program has contributed positively to mobilizing church members in fulfilling the Great Commission and supporting church multiplication.